(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2014)
An oleaginous fraction obtained from an alcohol extract of the fruit of Pterodon pubescens Benth. (FHPp) was microencapsulated in polymeric systems. These systems were developed using a complex coacervation method and consisted of alginate/medium-molecular-weight chitosan (F1-MC), alginate/chitosan with greater than 75% deacetylation (F2-MC), and alginate/low-molecular-weight chitosan (F3-MC). These developed systems have the potential to both mask the taste of the extract, and to protect its constituents against possible chemical degradation. The influence of the formulation parameters and process were determined by chemical profiling and measurement of the microencapsulation efficiency of the oleaginous fraction, and by assessment of microcapsule morphology. The obtained formulations were slightly yellow, odorless, and had a pleasant taste. The average diameters of the microcapsules were 0.4679 µm (F2-MC), 0.5885 µm (F3-MC), and 0.9033 µm (F1-MC). The best formulation was F3-MC, with FHPp microencapsulation efficiency of 61.01 ± 2.00% and an in vitro release profile of 75.88 ± 0.45%; the content of vouacapans 3-4 was 99.49 ± 2.80%. The best model to describe the release kinetics for F1-MC and F3-MC was that proposed by Higuchi; however, F2-MC release displayed first-order kinetics; the release mechanism was of the supercase II type for all formulations.